Effects of repetitive transcranial magnetic stimulation on lower extremity motor function and optimal parameters in stroke patients with different stages of stroke: a systematic evaluation and meta-analysis - Fan, Shiyu; Yan, Long; Zhang, Junfeng; Qian, Yulin; Wang, Meng; Yang, Lingqing; Yu, Tao (Frontiers in Neurology, 2024)
Background Repetitive transcranial magnetic stimulation (rTMS), as an emerging non-invasive neuromodulation technique, is now widely employed in rehabilitation therapy. The purpose of this paper is to comprehensively summarize existing evidence regarding rTMS intervention for lower limb motor function in patients at different stages of stroke. Methods A systematic search was conducted to identify randomized controlled trials (RCTs) assessing the efficacy of rTMS for treating lower limb motor dysfunction after stroke. Multiple databases, including China National Knowledge Infrastructure (CNKI), Wanfang Data Knowledge Service Platform, VIP Database, PubMed, Embase, Web of Science, and Cochrane Library, were searched. The search period extended from the inception of the libraries to June 2024. Literature information was extracted, and methodological quality was evaluated using the risk of bias assessment tool in the Cochrane Handbook. Meta-analysis was performed using Stata 17.0 software. Results Overall, 49 appropriate studies (including 3,558 stroke subjects) were found. Meta-analysis results demonstrated that rTMS effectively improved lower limb motor function across all stages of stroke. The intervention was particularly more effective in patients in the subacute stage than in the acute or chronic stages. Subgroup analysis revealed that, for acute-stage patients, low-frequency stimulation targeting the M1 or DLPFC brain regions on the unaffected side with 20–40 sessions significantly improved FMA-LE scores. In subacute-phase patients, low-frequency stimulation targeting the M1 brain regions on the unaffected side with 18 sessions significantly improved FMA-LE scores. The results demonstrated that HF-rTMS was more effective than LF-rTMS in improving walking speed, with the greatest efficacy observed at 20 sessions. While for enhancing gait balance in stroke patients, LF-rTMS with the best therapeutic effect was observed at a frequency of 20–40 treatments. Conclusion This study demonstrates the efficacy of rTMS in improving lower limb motor function, balance, and walking speed in stroke patients at various stages. The findings provide a valuable reference for the development of optimized rTMS treatment plans in clinical practice. Systematic review registration: PROSPERO: CRD42023466094.